16-CENTURY SHAIBANI DYNASTY IN MOVAROUNNAHR AND KHURASAN (Лучшие интеллектуальные исследования, 2025)
This article provides information about the consequences of the crisis of the Timurid state in the 16th century, the political situation in Movarounnahr on the eve of the establishment of the Shaybanid state. At the same time, this article reveals the emergence of a new state in our region - the state of Shaybanites, their efforts to unify the country. and relations with the Safavid state were also touched upon.